Faktor Yang Mempengaruhi Keberlanjutan Minat Pengguna Dalam Menggunakan Aplikasi Mhealth Melalui Variabel Satisfaction - Vania Katherine Hermawan; Eristia Lidia Paramita (University of Merdeka Malang, 2021)
The use of internet and smartphone has evolved. The rapid growth of innovation in technology allows them to become a high-functioning service provider through many of the applications available to help out humans fulfilling their needs. People demand quick and instant service provision, including health service. Applications based on mHealth technology are made to serve that demand. This research aims to examine the effects of intervening variables such as perceived usefulness, perceived ease of use, trust in application, and satisfaction on consumers’ continuance intention to use mHealth technology. This research employs a quantitative method to assess primary data samples taken from the users of Halodoc health service application in Java. The results of this research show that the trust and perceived usefulness variables do not significantly affect consumers’ continuance usage intention. Only the perceived ease of use and satisfaction variables yield a significant impact on consumers’ continuance usage intention. Hopefully, these results can be a valuable insight for PT Media Dokter Investama to enhance their service to attract more mHealth technology users to use Halodoc.